“The moment of testimonio is over”: theoretical issues and perspectives of testimonial studies - Fernández Benítez, Hans M. (Íkala, Revista de Lenguaje y Cultura, 2024)
The purpose of this text is to explore the main ideas and issues in the theory surrounding testimonial literature, and to analyze the discussions that brought the genre to a close; these discussions did not take into account the fact that the theoretical-methodological crisis affected the field of testimonial studies but did not affect the creation of new testimonies. Hence, the theory of testimonial literature in Latin America emerged from two works (Biography of a Runaway Slave and I, Rigoberta Menchú), is based on the Marxist concept of class struggle, and acknowledges only one type. Testimonies that do not fit this model have lost importance or been ignored. Although testimonial studies have entered a crisis, new testimonies continue to be produced. Finally, we posit the need to rekindle the debate based on different corpora and other categories of analysis. Received: 27-08-09 /Accepted: 24-09-09 How to reference this article: Fernandez Benitez, H. M. (2010). “The moment of testimonio is over”: problemas teóricos y perspectivas de los estudios testimoniales . Íkala 15(1), pp.47-71.